Education 4.0 : perception and challenges among academicians at a comprehensive university / Azuraidah Taib and Yunita Awang - Taib, Azuraidah; Awang, Yunita (2020)
The fourth industrial revolution (IR4.0) reflecting a new wave of technology in all aspects of business and industry. The IR 4.0 affects the business, governance and the people, with no exception the education sector which creating the buzzword of Education 4.0. In order for the IR4.0 to be embedded into education system, the participation and contribution of academicians are crucial. Their duty and responsibility to educate and produce students whom are ready for the 21st century job demands within IR4.0 digital age must be given a serious attention. As academicians, they are anticipated to relearn and equip themselves with the digital tools and ICT knowledge to align with the learning preference of the Gen Z students. However, what are their discernment and challenges towards Education 4.0? As such, this research attempts to investigate the academicians’ perception on Education 4.0 and to examine the challenges that are confronting them in aligning their tasks for Education 4.0. This research will use quantitative approach by means of questionnaire to gauge the academicians’ perceptions about Education 4.0. The questionnaire will be distributed to all academicians at UiTM Terengganu from three branches: Dungun, Kuala Terengganu and Bukit Besi. The findings will provide a vital view in education as the academicians are responsible in educating the students and should be ready in taking the challenge for producing a success and well-prepared individuals towards IR 4.0. Moreover, the academicians’ perceptions on Education 4.0 assist in connecting the teaching preferences of academicians which ultimately may affect the implementation of the Education 4.0 in the higher education institutions